LITTER CONTRIBUTION ON DIFFERENT GEOMORPHOLOGICAL CONDITIONS IN THE ATLANTIC FOREST – STATE OF RIO DE JANEIRO, BRAZIL - Mendonça, Victória Maria Monteiro; Santos, Gilsonley Lopes; Pereira, Marcos Gervasio Gervasio; Menezes, Carlos Eduardo Gabriel (Floresta, 2019)
The deposition of leaf litter on the forest floor is influenced by biotic and abiotic factors where forest fragments are inserted, which is a major source of nutrients to the soil. The objective of this study was to evaluate the influence of the change in relief conditions (landform) in leaf litter contribution and nutrient content in a Submontane Seasonal Semi-deciduous Forest in Pinheiral (state of Rio de Janeiro, Brazil). It was selected two adjacent landforms with convex and concave relief type and they divided into small sites (SS), obeying the variation of the slope and topographic gradient. Five conic collectors with an area of 0.2834 m² were installed in each SS, totaling 30 collectors. The collections of leaf litter were carried out every 30 days during a year. The material retained in the traps was separated as the fractions; leaves, twigs, reproductive and other material to assess the proportion of each fraction in the leaf litter production and nutrient content of the fraction leaves. The contribution and nutrient content of litter are influenced by the type of landform and seasons of the year. The highest contribution was observed in the dry season, in the lower and middle SS of the landforms, and the highest nutrient levels occurred in the convex landform during the rainy season.